Dual-energy CT angiography in imaging surveillance of endovascular aneurysm repair – Preliminary study results. Issue 148 (March 2022) - Charalambous, Stavros; Perisinakis, Kostas; Kontopodis, Nikolaos; Papadakis, Antonios E.; Maris, Thomas G.; Ioannou, Christos V.; Karantanas, Apostolos; Tsetis, Dimitrios
Highlights: CT angiography is the imaging modality of choice after endovascular aneurysm repair. Endoleak development is the drawback of endovascular aneurysm repair. Dual-energy CT imaging may efficiently identify suspicious type II endoleak lesions for aneurysm expansion. Low-keV monochromatic images improve the conspicuity for the detection of type II endoleaks. Abstract: Purpose: To investigate the value of dual-energy CT imaging to discriminate low- from high- risk type II endoleaks (T2EL) after endovascular aneurysm repair (EVAR). Method: Study participants were consecutive patients referred for CT at 1-month post-EVAR. CT imaging acquisition included a dual-energy CT angiography (DECTA) and a delayed single-energy CT (SECT) imaging. Patients diagnosed with T2EL were re-examined at 6-months post-EVAR to assess the aneurysm sac growth (ASG). Upon ASG recorded, patients were categorized as having low- (group A) or high- risk (group B) T2EL. DECTA image data were employed to calculate the normalized effective atomic number (NZeff ), the normalized iodine concentration, the slope of HUendoleak /HUaorta against monochromatic energy, the dual-energy index and an improvised endoleak index (EI) for each T2EL. Statistical analysis was employed to compare all above parameters regarding their ability to differentiate low- from high- risk T2EL. Results: Among 40 patients examined at 1-month post-EVAR, 14 patients were diagnosed with T2EL. NZeff and EI were found to be significantly lower in group A. NZeff was found to have the highest power to discriminate high-risk T2EL with an area-under-curve of 86.7%, showing100% specificity and 60% sensitivity. The optimal contrast-to-noise ratio for T2EL demonstrated a median peak conspicuity level at 54-keV. The mean effective dose from DECTA and SECT scans was 27.8% lower compared to the sum of three SECT acquisitions. Conclusions: NZeff and EI were found to have a significant power in predicting the aggressiveness of T2EL lesions. Virtual monochromatic images at 54-keV may enhance T2EL detection efficiency.